Ultrasound characteristics of thyroid nodules diagnosed as follicular neoplasms by fine-needle aspiration cytology - Cordes, Michael; Nagel, Holger; Horstrup, Karen; Sasiadek, Marek; Kuwert, Torsten (Nuklearmedizin - NuclearMedicine, 2016)
Cytopathological evaluation has been proven useful in the diagnostic work-up of “cold” nodules. The cytological diagnosis of follicular neoplasm usually requires histology to exclude malignancy. The objective of this prospective study was to test the hypothesis that ultrasound examinations show distinct characteristics in a subgroup of nodules which may attest the benign nature of a follicular neoplasm. Patients, methods: 56 patients (45 women, 11 men) were included in the study. All patients had a “cold” nodule which was diagnosed as follicular neoplasm. Consecutive histology revealed follicular adenomas (FTAs) (n = 44), follicular carcinomas (FTCs) (n = 7) and papillary carcinomas (PTCs) (n = 5), including follicular variant papillary carcinomas (fv PTCs) (n = 4). Ultrasound examinations were performed preoperatively. The ultrasound examinations were evaluated with respect to seven characteristics. Results: In 21 % of patients a follicular neoplasm was associated with a malignant and in 79 % of patients with a benign tumor as compared with histology. The ultrasound characteristics size 2 ml, round shape and homogeneous structure revealed significant differences for FTAs, FTCs and PTCs with p < 0.001, p = 0.003 and p = 0.027, resp. With respect to the benign nature of a follicular neoplasm maximum values for sensitivity and specificity were 0.75 and 0.83. Multivariate discriminant analysis revealed that ultrasound criteria were suitable to discriminate between benign vs. malignant nodules and among FTAs, FTCs and PTCs with correlation coefficients of r = 0.53 and r = 0.74, resp. Conclusions: in selected patients with higher operative risks and cytological diagnosis of follicular neoplasm ultrasound parameters may be helpful to assume a benign nature of the neoplasm and thus avoid the necessity of a histological work-up.
Keywords: Ultrasound; fine-needle aspiration biopsy; cyto logy; follicular neoplasms; follicular adenomas; follicular carcinomas